Diagnostico temprano del síndrome de Bandl Frommel Pinard en la rotura uterina - Fernandez Cabrera, Stefany Nicole (Machala : Universidad Técnica de Machala, 2024)
Uterine rupture during pregnancy is an important and rare, but potentially catastrophic, complication that constitutes an obstetric emergency due to its high rate of morbidity and mortality for both the mother and the fetus. This phenomenon occurs most frequently in previously scarred uteruses, as a result of cesarean sections or uterus-related surgeries, although it can also occur in unscarred uteruses, although less commonly and with potentially more serious consequences. The diagnosis of uterine rupture can be challenging due to the variability in clinical presentation, which can include acute abdominal pain, changes in fetal heart rate, abnormal vaginal bleeding, and signs of maternal shock. Clinical suspicion is reinforced when symptoms are nonspecific, but are accompanied by a relevant clinical history and physical findings consistent with intra-abdominal hemorrhage. Objective: Early identify the signs and symptoms of uterine rupture during pregnancy and childbirth to prevent serious obstetric complications and reduce maternal-fetal morbidity and mortality. Methodology: A bibliographic review of scientific articles from the last 5 years was carried out on the platforms “PubMed”, “MedScape” and “Scielo”. Conclusion: Bandl's sign has a high suspicion of obstruction of the birth canal in the second stage, which could eventually cause uterine rupture or imminent uterine rupture along with other signs such as Frommel and Pinard, its early detection allows adequate management by part of health personnel, thus reducing morbidity and mortality rates.
La rotura uterina en la gestación es una complicación importante y poco común, pero potencialmente catastrófica, que constituye una emergencia obstétrica debido a su alto índice de morbimortalidad tanto para la madre como para el feto. Este fenómeno ocurre más frecuentemente en úteros con cicatrices previas, como resultado de cesáreas o cirugías relacionadas con el útero, aunque también puede ocurrir en úteros sin cicatrices, aunque menos comúnmente y con consecuencias potencialmente más graves. El diagnóstico de rotura uterina puede ser desafiante debido a la variabilidad en la presentación clínica, que puede incluir dolor abdominal agudo, cambios en la frecuencia cardíaca fetal, sangrado vaginal anormal y signos de shock materno. La sospecha clínica se refuerza cuando los síntomas son inespecíficos, pero se acompaña de una historia clínica relevante y hallazgos físicos consistentes con hemorragia intraabdominal. Objetivo: Identificar de manera temprana los signos y síntomas de la ruptura uterina durante el embarazo y el parto para prevenir complicaciones obstétricas graves y reducir la morbilidad y mortalidad materno-fetal. Metodología: Se llevó a cabo una revisión bibliográfica de artículos científicos de los 5 últimos años, en las plataformas “PubMed”, “MedScape” y “Scielo”. Conclusión: El signo de Bandl posee una alta sospecha de obstrucción del canal de parto en segunda etapa lo que eventualmente podría provocar una rotura uterina o rotura uterina inminente junto con otros signos como el de Frommel y Pinard, su temprana detección permite un adecuado manejo por parte del personal de salud reduciendo así las tasas de morbimortalidad.
Keywords: RUTURA UTERINA; SIGNO DE BANDL; SINGO DE FROMMEL; SIGNO DE PINARD